A model of racing kayak surge motion a numerical approach with realistic oscillating propulsion forces - Juhl, J. Ø.; de Zee, M.; Klitgaard, K. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
This study presents a novel forward dynamics model of racing kayak surge motion. The model, driven by adjustable oscillating propulsion forces, replicates true paddle stroke forces. It is based on Newton`s second law of motion, with the net force comprising of propulsion force, skin friction drag, wave-making drag, form drag, and air drag. The total mass includes the kayak, paddler, and added mass. The fourth-order Runge-Kutta method is used to solve for speed and distance. The model incorporates a unique hull formulation for wetted surface area estimation, Michell`s integral for wave-making drag, and a log wind profile with allometric scaling for air drag. It accounts for varying stature height, body mass, kayak dimensions, wind speed, and stroke propulsion profiles. The model is a significant advancement in its domain, with broad applicability for the future. It aligns with existing data and analyses, but validation data is limited.